2015
DOI: 10.31768/2312-8852.2015.37(3):208-212
|View full text |Cite
|
Sign up to set email alerts
|

TRP Genes Family Expression in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the most common cancer of the gastrointestinal tract. Different factors are responsible for the development of CRC. Transient Receptor Potential (TRP) which is an important component of calcium channel is associated with several pathological conditions like cancer, neurodegenerative and cardiovascular diseases. Thirty members of the family of TRP ion channel in mammals have been determined till now. The aim of this study is to investigate TRPM, TRPV and TRPC gene expression levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
1
27
0
5
Order By: Relevance
“…Aberrant KCTD5‐mediated regulation of TRPM4 could also play a role in the pathophysiology of numerous diseases that have been linked to a gain‐of‐function in TRPM4 activity 49‐54,74 . In particular, a number of studies have reported elevated expression of TRPM4 in cancer 6,7,43,48 . For instance, TRPM4 promotes cell migration and promotes epithelial to mesenchymal transition of prostate cancer cells, 9 and recent evidence supports using TRPM4 expression as a clinical biomarker for biochemical recurrence in prostate cancer implicated in cell migration and proliferation of malignant cells 8‐10,43,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant KCTD5‐mediated regulation of TRPM4 could also play a role in the pathophysiology of numerous diseases that have been linked to a gain‐of‐function in TRPM4 activity 49‐54,74 . In particular, a number of studies have reported elevated expression of TRPM4 in cancer 6,7,43,48 . For instance, TRPM4 promotes cell migration and promotes epithelial to mesenchymal transition of prostate cancer cells, 9 and recent evidence supports using TRPM4 expression as a clinical biomarker for biochemical recurrence in prostate cancer implicated in cell migration and proliferation of malignant cells 8‐10,43,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Several TRP channels have been shown to be dysregulated in CRC. A study investigating mRNA expression levels of the TRP channels in human CRC tissue versus normal colon mucosa detected an increase in gene expression of TRPM8, TRPV6, and TRPV1 and a lower expression of TRPV4, TRPM4, TRPV3, TRPC6, and TRPV5 in the tumor tissues of CRC compared to normal tissues [119]. Table 6 summarizes studies in which the expression of TRP channels in human gastric cancer samples was described.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Therefore, TRPM4 is regarded to be a negative regulator of Ca 2+ signaling [137][138][139][140]. Reports on mRNA expression levels of TRPM4 in colorectal cancer either found it to be lower in CRC tissue compared to normal colon tissue [119], or no differences were detected [141]. However, a recent study investigating TRPM4 protein expression levels in CRC tissues showed that its high expression correlates with high numbers of tumor buds and an increased percentage of infiltrative tumor border configuration.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…TrpC6 is amongst the latter subgroup of TrpC channels. 283 Of clinical relevance, TrpC6 channels are upregulated in a wide range of cell types across a broad spectrum of disease indications, such as focal segmental glomerulosclerosis (FSGS), 161 pulmonary fibrosis, 284 cancer, [285][286][287][288][289][290] hypertension 291,292 and allergic asthma. 293 Expression or over-expression of TrpC6 has been shown to have a pro-proliferative effect.…”
Section: Trpc6mentioning
confidence: 99%